Diversity analysis of KAU released cocoa (Theobroma cacao L.) varieties based on morphological parameters - Sajeevkumar, Sujith S; Minimol, J.S.; Ajmal, P.M.; Suma, B. (Journal of Tropical Agriculture, 2017)
Cross incompatibility is a major constraint in cocoa research and understanding similarity or dissimilarity among the varieties before establishing clonal gardens is essential for propagation and further improvement. Morphological analysis with respect to the selected quantitative and qualitative pod characters were taken for the present diversity analysis. Six qualitative and eight quantitative pod and bean characters of each variety were recorded as per the standard descriptors. The genetic associations among the varieties were estimated through Jaccard’s similarity coefficients using NTSYSpc version 2.1. Cluster analysis was done on the similarity matrix and dendrogram was constructed using Unweighted Pair-Group Method (UPGMA). Diversity analysis based on qualitative and quantitative traits grouped the ten cocoa varieties into five clusters at 68 per cent similarity level. Homology between qualitative and quantitative clustering pattern was also worked out and significant variation was observed in distribution pattern of varieties under study. The polyclonal garden layout designed based on the present diversity analysis can be made use of for ensuring maximum pod set when cocoa is intercroped with coconut.